2006
DOI: 10.1177/153537020623100807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Commensal Bacteria on Intestinal Morphology and Expression of Proinflammatory Cytokines in the Gnotobiotic Pig

Abstract: A germ-free neonatal pig model was established to determine the effects of bacterial colonization by different species on small intestinal morphology and proinflammatory cytokine gene expression. Two experimental groups of 16 pigs were aseptically delivered by cesarian section and allocated into 4 gnotobiotic isolators. Pigs were either maintained germ-free (GF), or were orally inoculated with either a single strain of nonpathogenic Escherichia coli (EC) or Lactobacillus fermentum (LF) or conventionalized with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
118
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(139 citation statements)
references
References 37 publications
20
118
0
1
Order By: Relevance
“…Reduced crypt depth and increased villus length agree with the previous observations in germ-free pigs (Kenworthy, 1970;Thompson, and Trexler, 1971;Wostmann, 1975;Shurson et al, 1990;Shirkey et al, 2005). In the present study villi were the longest in the jejunum and shortest in the duodenum and ileum, whereas crypt depth was shortest in the jejunum and deepest in the duodenum throughout the observation period (Figures 5 and 6).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Reduced crypt depth and increased villus length agree with the previous observations in germ-free pigs (Kenworthy, 1970;Thompson, and Trexler, 1971;Wostmann, 1975;Shurson et al, 1990;Shirkey et al, 2005). In the present study villi were the longest in the jejunum and shortest in the duodenum and ileum, whereas crypt depth was shortest in the jejunum and deepest in the duodenum throughout the observation period (Figures 5 and 6).…”
Section: Discussionsupporting
confidence: 82%
“…The mechanisms affecting intestinal length are unknown, however, it can be hypothesized that increased small intestine length in conventionalized pigs is a compensatory response to the decreased absorptive capacity associated with decreased surface area (decreased villus length) and/ or to direct competition with the microbiota for dietary nutrients. Shirkey et al (2005) observed that in the proximal region of the small intestine, the relative weights for segments from conventional pigs tended to be higher than those from germ-free and monoassociated pigs. This is consistent with the previous reports indicating that compared with germ-free animals, conventionally reared animals experience intestinal "thickening" associated primarily with increased lamina propria cellularity (Miniats and Valli, 1973) as well as thickening of the submucosa and muscular layers (Shurson et al, 1990;Furuse and Okumura, 1994;Gaskins, 1997).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Segmental differences were also found in comparative studies conducted on germ free and conventional animals. Shirkey et al (2006) have reported that villus height was the longest in jejunum of pigs supplemented with Lactobacillus fermentum. On the other hand Shurson et al (1990) reported that germ-free pigs had longer ileal and duodenal villi, but shorter jejunal villi compared with their conventional counterparts.…”
Section: Villus Heightmentioning
confidence: 99%